Unusual manifestations of type II cryoglobulinaemia associated with Waldenström's macroglobulinaemia. Issue 11 (1st November 2000) - Blanco, P; Viallard, J-F; Rivel, J; Leng, B; Pellegrin, J-L
Abstract : Cryoglobulinaemia in association with Waldenström's macroglobulinaemia is relatively common, ranging from 8% to 18% of cases; however, < 5% have symptoms or complications. We describe a patient with a history of cutaneous, peritoneal, and fallopian tube vasculitis related to type II cryoglobulinaemia associated with Waldenström's macroglobulinaemia. Cytotoxic treatment was initiated (cyclophosphamide, vincristine, and prednisone) and had a good initial response. However, after the third course of chemotherapy, the patient presented with septic shock and died. Even though cryoglobulinaemia is a model of systemic vasculitis, peritoneal and fallopian tube vasculitis associated with type II cryoglobulinemia has not been described previously.